Composite magnetic material and metal composite core

The integration of a telechelic acrylic polymer with acryloyl groups into the resin of a composite magnetic material enhances the high-temperature magnetic performance of metal composite cores, ensuring reduced iron loss and increased strength even at elevated temperatures.

JP2025046706APending Publication Date: 2025-04-02TAMURA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023154948
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing metal composite cores used in coil components, such as reactors, face challenges in maintaining good magnetic properties at high temperatures, particularly when exposed to temperatures as high as 200°C for extended periods.

Method used

A composite magnetic material is developed by mixing magnetic powder with a resin that includes an epoxy resin and a telechelic acrylic polymer with acryloyl groups. This mixture is then cured to form a metal composite core with enhanced high-temperature magnetic performance.

Benefits of technology

The resulting metal composite core maintains excellent magnetic properties, including reduced iron loss and increased strength, even after exposure to 200°C for 1000 hours, thereby addressing the temperature-related challenges faced by existing cores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025046706000001
    Figure 2025046706000001
  • Figure 2025046706000002
    Figure 2025046706000002
  • Figure 2025046706000003
    Figure 2025046706000003
Patent Text Reader

Abstract

To provide a metal composite core which can maintain good magnetic characteristics, even in a case of being exposed under high temperature environment for a long period of time.SOLUTION: A metal composite core is obtained by mixing magnetic powder with a resin and curing the resin, wherein the resin contains an epoxy resin. A telechelic acrylic polymer having an acryloyl group is added to the resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite magnetic material in which magnetic powder and resin are mixed, and a metal composite core formed by curing the resin of the composite magnetic material. [Background technology]

[0002] Coil components such as reactors are used in a variety of applications, including office equipment, solar power generation systems, and automobiles. Coil components have a coil attached to a core that contains a magnetic material. Known cores include powder magnetic cores and metal composite cores.

[0003] Powder magnetic cores are formed by compacting soft magnetic powder and an insulating coating that covers the soft magnetic powder. The pressure during compacting is quite high, on the order of several tons to several tens of tons, to compact the magnetic powder.

[0004] On the other hand, metal composite cores are formed by preparing a composite magnetic material by mixing magnetic powder and resin, and then curing the resin of the composite magnetic material. Since the composite magnetic material is clay-like, the metal composite core is prepared by pouring the composite magnetic material into a container and curing it. Therefore, metal composites have a high degree of freedom in terms of shape. Therefore, metal composite cores with a high degree of freedom in terms of shape have been attracting attention in recent years. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-017326 A Summary of the Invention [Problem to be solved by the invention]

[0006] Coil components are required to have magnetic properties such as iron loss. For example, coil components used in voltage step-up and step-down converters are required to improve energy conversion efficiency, so they are required to reduce iron loss, which is an energy loss.

[0007] In recent years, as the applications of coil components have become more diverse, they may be exposed to high temperatures of up to 200° C. Therefore, there is a demand for metal composite cores that can maintain good magnetic properties even when exposed to such high-temperature environments for long periods of time.

[0008] The object of the present invention has been proposed to solve the above problems, and is to provide a composite magnetic material and a metal composite core that can maintain good magnetic properties even when exposed to a high-temperature environment for a long period of time. [Means for solving the problem]

[0009] The composite magnetic material of the present invention is a composite magnetic material in which a magnetic powder and a resin are mixed, characterized in that the resin contains an epoxy resin, and a telechelic acrylic polymer having an acryloyl group is added to the resin.

[0010] The metal composite core of the present invention is characterized in that it is formed by curing the resin of the composite magnetic material. Effect of the Invention

[0011] According to the present invention, it is possible to obtain a metal composite core that can maintain good magnetic properties even when exposed to a high-temperature environment for a long period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (Embodiment) The composite magnetic material and metal composite core according to the embodiment will be described. The composite magnetic material is made by mixing magnetic powder and resin. The metal composite core (hereinafter referred to as "MC core") is a core made by hardening the resin of this composite magnetic material. The MC core is used as a magnetic body for coil components such as reactors.

[0013] As the magnetic powder constituting the composite magnetic material, a soft magnetic powder can be used, and in particular, Fe powder, Fe-Si alloy powder, Fe-Al alloy powder, Fe-Si-Al alloy powder (Sendust), amorphous alloy powder, nanocrystal, or a mixture of two or more of these powders can be used. As the Fe-Si alloy powder, for example, Fe-6.5% Si alloy powder or Fe-3.5% Si alloy powder can be used.

[0014] The magnetic powder may be one having a different average particle size. In other words, the magnetic powder may be composed of a first magnetic powder and a second magnetic powder having an average particle size smaller than that of the first magnetic powder. In this specification, the average particle size refers to D50 (median diameter) unless otherwise specified. In addition, the first magnetic powder and the second magnetic powder may be the same or different types.

[0015] The average particle size of the first magnetic powder is preferably 100 μm to 200 μm, and that of the second magnetic powder is preferably 3 μm to 10 μm. By setting the sizes in these ranges, the second magnetic powder having a smaller average particle size can be inserted into the gaps between the first magnetic powder particles, improving the density and magnetic permeability while reducing iron loss.

[0016] The weight ratio of the first magnetic powder to the second magnetic powder is preferably first magnetic powder:second magnetic powder=80:20 to 60:40. By setting the ratio within this range, the density and magnetic permeability can be improved and the iron loss can be reduced.

[0017] The resin that constitutes the composite magnetic material is mixed with the magnetic powder and is interposed between the magnetic powder particles. More specifically, the resin does not cover the magnetic powder particles, but fills the gaps between the magnetic powder particles. The addition of the resin bonds the magnetic powder particles together.

[0018] The resin includes an epoxy resin. In addition to the epoxy resin, a thermosetting resin, an ultraviolet curing resin, or a thermoplastic resin may be further added. As the thermosetting resin, a phenol resin, an unsaturated polyester resin, a polyurethane, a diallyl phthalate resin, a silicone resin, or the like can be used. As the ultraviolet curing resin, a urethane acrylate-based, an epoxy acrylate-based, or an acrylate-based resin can be used. As the thermoplastic resin, it is preferable to use a resin having excellent heat resistance, such as a polyimide or a fluororesin.

[0019] The resin is preferably contained in the range of 3 wt% to 5 wt% of the magnetic powder (the total amount of the first and second magnetic powders when the magnetic powder is composed of the first and second magnetic powders). If the resin content is less than 3 wt%, the bonding strength of the magnetic powders is insufficient, and the mechanical strength of the MC core is reduced. If the resin content is more than 5 wt%, the magnetic properties of coil components such as reactors may deteriorate.

[0020] Furthermore, additives are added to the resin. An example of the additive is a telechelic acrylic polymer having an acryloyl group. The telechelic acrylic polymer is a liquid resin that retains liquid at room temperature. In addition, the telechelic acrylic polymer has reactive functional groups at both ends, as shown in the following chemical formula (1). (chemical formula 1) TIFF2025046706000001.tif43147R 1 and R 2 are each independently a hydrogen atom or an alkyl group.

[0021] The reactive functional group represented by X or Y in the above chemical formula (1) is, but is not limited to, represented by the following chemical formulas (2) and (3). (Chemical formula 2) TIFF2025046706000002.tif58116 (chemical formula 3) TIFF2025046706000003.tif55132

[0022] When X or Y in the above formula (1) is an alkoxysilyl group represented by the above formula (2), the curing type is a condensation type (moisture).When X or Y in the above formula (1) is an acryloyl group represented by the above formula (3), the curing type is a radical reaction type.

[0023] In the telechelic acrylic polymer, X and Y in the above chemical formula (1) may be different types of reactive functional groups, but it is particularly preferable that the reactive functional groups of X and Y at both ends are both acryloyl groups. By making the functional groups at both ends acryloyl groups, good core loss and strength can be maintained even when exposed to high temperatures such as 200°C for a long period of time.

[0024] The viscosity of the telechelic acrylic polymer is preferably 160 (Pa·s) or more and 530 (Pa·s) or less. If the viscosity is lower than 160 (Pa·s), there is a risk that the heavy powder will settle during curing. On the other hand, if the viscosity is higher than 530 (Pa·s), the polymer will not have viscosity and the powder will have poor flowability, making it difficult to mold the MC core.

[0025] It is preferable that the chain length of the telechelic acrylic polymer is uniform. A telechelic acrylic polymer with a uniform chain length can be produced, for example, by living radical polymerization technology. The uniform chain length of the telechelic acrylic polymer results in an ideal crosslinked structure as shown in the following chemical formula (4), and good core loss and strength can be maintained even when exposed to high temperatures such as 200°C for a long period of time. (Chemical formula 4) TIFF2025046706000004.tif84162

[0026] In addition, the telechelic acrylic polymer is preferably one that is cured by a radical reaction. In particular, a thermosetting or ultraviolet curing one is preferable, and a thermosetting one is more preferable. As described above, since the resin contains an epoxy resin, which is a thermosetting resin, the telechelic acrylic polymer is cured simultaneously with the epoxy resin. By curing the telechelic acrylic polymer and the epoxy resin simultaneously, the strength of the MC core is increased.

[0027] Next, the manufacturing method of the composite magnetic material and the MC core will be described. The manufacturing method of the composite magnetic material includes (1) a resin mixing step and (2) a powder mixing step. The manufacturing method of the MC core includes (3) a pressure molding step and (4) a curing step after (2) the powder mixing step.

[0028] (1)Resin mixing process The resin mixing step is a step of mixing a resin containing an epoxy resin with a telechelic acrylic polymer. The resin and the telechelic acrylic polymer can be mixed automatically or manually using a predetermined mixer. The mixing time can be set appropriately, for example, for 2 minutes. Through the resin mixing step, a mixed resin in which the resin and the telechelic acrylic polymer are mixed is produced.

[0029] (2) Powder mixing process The powder mixing process is a process in which magnetic powder is added to the mixed resin and mixed. The mixed resin and magnetic powder can be mixed automatically or manually using a specified mixer. The mixing time can be set appropriately, for example, for 2 minutes. A composite magnetic material is produced through the powder mixing process. When a first magnetic powder and a second magnetic powder are used as the magnetic powder, the first magnetic powder and the second magnetic powder may be mixed to produce a mixed powder before the powder mixing process, and then the mixed powder may be added to the mixed resin. (3) Pressure molding process The pressure molding process is a process in which pressure is applied to mold the MC core to fit its shape. In the pressure molding process, first, a composite magnetic material is filled into a container that matches the shape of the MC core to be manufactured. The composite magnetic material filled in the container is then pressed with a pressing member. By applying pressure with this pressing member, the composite magnetic material is expanded to fit the shape of the container and the voids contained in the composite magnetic material are reduced, thereby increasing the density of the MC core.

[0030] Unlike powder magnetic cores, which are formed by compressing magnetic powder with a few tons to a few tens of tons, the pressure applied to the composite magnetic material is low, at a few to a few tens of kg. Therefore, while the magnetic powder in powder magnetic cores deforms, the magnetic powder in MC cores does not deform even when pressure is applied. Note that, since applying pressure is not an essential requirement for molding MC cores, as is the case with powder magnetic cores, the (3) pressure molding step may be omitted.

[0031] (4) Curing process The curing process is a process for curing the resin contained in the composite magnetic material. Since the resin contains epoxy resin, which is a thermosetting resin, the resin is cured by applying heat. In addition, when a resin other than a thermosetting resin is contained, the resin may be further cured by an appropriate method depending on the type of resin.

[0032] (Example) The present invention will be described in more detail with reference to examples. Note that the present invention is not limited to the following examples. MC cores of Examples 1 and 2 and Comparative Examples 1 to 3 were produced. The MC cores of Examples 1 and 2 and Comparative Examples 1 to 3 differ only in the presence or absence of addition of a telechelic acrylic polymer or the type of telechelic acrylic polymer, and the other materials, production methods, and production conditions are the same.

[0033] First, various telechelic acrylic polymers were prepared. The telechelic acrylic polymers prepared are as shown in Table 1 below, and they have in common the fact that they have reactive functional groups at both ends. Type A telechelic acrylic polymer has acryloyl groups at both ends, a radical reaction type curing system, a viscosity of 160 (Pa·s), and a glass transition point of -50 (℃). Type B telechelic acrylic polymer has acryloyl groups at both ends, a radical reaction type curing system, a viscosity of 530 (Pa·s), and a glass transition point of -39 (℃). Type C telechelic acrylic polymer has alkoxysilyl groups at both ends, a condensation type (moisture) curing system, a viscosity of 70 (Pa·s), and a glass transition point of -50 (℃). Type D telechelic acrylic polymer has reactive functional groups at both ends that are alkoxysilyl groups, a condensation curing type (moisture), a viscosity of 1100 (Pa·s), and a glass transition point of -39 (℃).

[0034] [Table 1]

[0035] In Example 1, a telechelic acrylic polymer of type A was used. In Example 2, a telechelic acrylic polymer of type B was used. In Comparative Example 2, a telechelic acrylic polymer of type C was used. In Comparative Example 3, a telechelic acrylic polymer of type D was used. In Comparative Example 1, no telechelic acrylic polymer was added.

[0036] An epoxy resin was used as the resin. The epoxy resin was added in an amount of 3.75 wt% relative to the total amount of the first magnetic powder and the second magnetic powder. In Examples 1 and 2 and Comparative Examples 2 and 3, various telechelic acrylic polymers were added in an amount of 10 wt% relative to the amount of epoxy resin added. The added telechelic acrylic polymer and epoxy resin were then mixed.

[0037] In Examples 1 and 2 and Comparative Examples 2 and 3, the magnetic powder was mixed with the mixed telechelic acrylic polymer and epoxy resin. On the other hand, in Comparative Example 1, the magnetic powder was mixed with the epoxy resin. Two types of magnetic powder, a first magnetic powder and a second magnetic powder, having different average particle diameters (median diameter D50), were prepared. The average particle diameter of the first magnetic powder was 150 μm. The average particle diameter of the second magnetic powder was 5 μm. The weight ratio of the first magnetic powder to the second magnetic powder was 70:30. Fe-6.5Si was used for both the first magnetic powder and the second magnetic powder. First, the first magnetic powder and the second magnetic powder were mixed to prepare a mixed powder, and then the mixed powder was added to and mixed with the telechelic acrylic polymer and the epoxy resin to prepare a composite magnetic material. Mixing was performed by hand mixing.

[0038] After the composite magnetic material was prepared, it was placed in a mold and pressure molded at 1.0 kN. After pressure molding, the telechelic acrylic polymer and the epoxy resin were cured. The curing conditions were drying at a temperature of 150°C for 4 hours. In this manner, the MC cores of Examples 1 and 2 and Comparative Examples 1 to 3 were prepared.

[0039] Each MC core was exposed to a temperature of 200°C for 1000 hours. The strength and core loss were measured after 1000 hours. The size of the MC core was 26.0 mm in outer diameter, 15.0 mm in inner diameter, and 10 mm in height.

[0040] The strength is radial crushing strength. The strength was measured using a tension and compression tester (Japan Measurement Systems: MAX intelligent load tester). The strength measurement conditions were a measurement speed of 0.5 mm / min.

[0041] The iron loss was measured by making a reactor using each of the MC cores. The reactor was made by winding a 10-turn primary winding and a 10-turn secondary winding with φ1.0mm copper wire around each MC core. The iron loss measurement conditions were a frequency of 30kHz and a maximum magnetic flux density Bm=20mT.

[0042] The iron loss was calculated using a magnetic measuring device, a BH analyzer (Iwatsu Measurement Corporation: SY-8219). This calculation was performed by calculating the hysteresis loss coefficient and eddy current loss coefficient from the iron loss frequency curve using the least squares method with the following equations (1) to (3).

[0043] Pcv = Kh×f + Ke×f 2 (1) Ph = Kh × f (2) Pe = Ke × f 2 (3) Pcv: Iron loss Kh: Hysteresis loss coefficient Ke: Eddy current loss coefficient f: frequency Ph: Hysteresis loss Pe: Eddy current loss

[0044] The rate of change in iron loss was then calculated by comparing the iron loss before (0 hours) and after 1000 hours of exposure to a temperature of 200°C, and was calculated using the following formula (4). Iron loss change rate (%) = (iron loss Pcv (1000 hours) - iron loss Pcv (0 hours)) / iron loss Pcv (0 hours) × 100 (4) The results of the above measurements are shown in Table 2.

[0045] [Table 2]

[0046] As shown in Table 2 above, Examples 1 and 2 using telechelic acrylic polymer type A or B have a lower iron loss change rate than Comparative Example 1, which does not contain telechelic acrylic polymer, and Comparative Examples 2 and 3, which use telechelic acrylic polymer type C or D. That is, Examples 1 and 2 maintain good values ​​even after being exposed to 200°C for 1000 hours. Therefore, it was confirmed that the presence of an acryloyl group in the telechelic acrylic polymer increases heat resistance and allows good iron loss to be maintained.

[0047] Moreover, the strength of Examples 1 and 2 is 85 (Mpa) or more, which is about 20 (Mpa) higher than that of Comparative Examples 1 and 2, and thus is high. On the other hand, the strength of Comparative Example 3 is higher than that of Examples 1 and 2, but the iron loss change rate is more than three times that of Examples 1 and 2. Therefore, it was confirmed that good iron loss and high strength can be maintained by adding a telechelic acrylic polymer having an acryloyl group to the resin.

[0048] (Other embodiments) In this specification, an embodiment of the present invention has been described, but this embodiment is presented as an example and is not intended to limit the scope of the invention. The above-mentioned embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention.

Claims

1. A composite magnetic material in which magnetic powder and resin are mixed, The resin includes an epoxy resin, a telechelic acrylic polymer having an acryloyl group is added to the resin; A composite magnetic material characterized by:

2. The telechelic acrylic polymer has acryloyl groups at both ends; The composite magnetic material according to claim 1 .

3. The telechelic acrylic polymer has a uniform chain length; The composite magnetic material according to claim 1 .

4. The viscosity of the telechelic polymer is 160 (Pa·s) or more and 530 (Pa·s) or less; The composite magnetic material according to claim 1 .

5. The composite magnetic material according to any one of claims 1 to 4, wherein the resin is cured. Featuring a metal composite core.

Citation Information

Patent Citations

  • Composite material, reactor-use core, and reactor

    JP2017017326A